2007
DOI: 10.1063/1.2769660
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced forces on two nearby spheres

Abstract: Flow-induced forces on two identical nearby spheres at Re= 300 were numerically studied. We consider all possible arrangements of the two spheres in terms of the distance between the spheres and the angle inclined with respect to the main flow direction. It turns out that significant changes in the characteristics of vortex shedding are noticed depending on how the two spheres are positioned, resulting in quantitative changes of force coefficients on both spheres. Collecting all the numerical results obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The vorticity imbalance between the top and bottom regions of the reference particle brings about a net torque exerted on the particle. The interpretation of the PDFs emerging from our analysis is consistent with the observations made with a binary system of two spheres exhibiting the same dependency of the forces on relative positions of the spheres (Prahl et al 2007;Yoon & Yang 2007). Such modification of the forces and torques were also elucidated by Akiki et al (2016).…”
Section: Probability Distribution Mapssupporting
confidence: 89%
“…The vorticity imbalance between the top and bottom regions of the reference particle brings about a net torque exerted on the particle. The interpretation of the PDFs emerging from our analysis is consistent with the observations made with a binary system of two spheres exhibiting the same dependency of the forces on relative positions of the spheres (Prahl et al 2007;Yoon & Yang 2007). Such modification of the forces and torques were also elucidated by Akiki et al (2016).…”
Section: Probability Distribution Mapssupporting
confidence: 89%
“…The case of fixed bodies placed side by side has received equal attention when the wakes of the bodies are unsteady. For a Reynolds number of 300 corresponding to unsteady wakes for solid spheres, Yoon & Yang (2007) found numerically that spheres placed side by side repel one another for all the relative distances investigated, namely ∆ h 5, indicating that repulsion between two side-by-side fixed spheres occurs for separation distances that are larger for unsteady wakes than for steady ones. Results related to the interaction between the unsteady wakes of the bodies were also provided.…”
Section: Introductionmentioning
confidence: 89%
“…They studied mainly the flow around the particles and concluded that for H/D0=1 (particles are in contact) the particles act as a rigid bluff body, while for H/D0≥2 the interaction between the shedding vortices is minimized as well as the effect of the jet-like flow occurring through them. Numerical studies of similar particle arrangements were performed by Folkersma et al [9], Tsuji et al [10], Ardekani et al [11], Prahl et al [12], Yoon and Yang [13] and by Jadoon [14]. The Re numbers examined range from 5•10 -7 up to 600, while the non-dimensional distance between the particles are in the range of 1 up to 23.…”
Section: Introductionmentioning
confidence: 91%